Los fríjoles colombianos Lima y común: puntos de vista de su origen y el significado de su evolución - Debouck, Daniel G. (1996)
This article reviews the geographical distribution of wild common and lima beans in the Neotropics, their morphological and ecological attributes, and their biochemical and molecular variation along their ranges. These facts reveal the organization of the genetic diversity into three major gene pools, with one being considered ancestral and additional subdivisions within the derived ones. The relationships between the ancestral branch and related species are discussed. Colombia appears to be more than a place of contact between gene pools of cultivated materials, but the transit place of the ancestral branches, and a possible place of domestication as well.